PENGEMBANGAN PERMAINAN SIMULASI KETERBUKAAN DIRI UNTUK SISWA SMP - Jannah, Roichatul; Zen, Ella Faridati; Muslihati, Muslihati (Jurnal Kajian Bimbingan dan Konseling, 2016)
This development study produced a guide for counselors and a self-disclosure simulation game media that was used to increase self-disclosure in junior high school students. This development research uses the Borg & Gall (1983) model: conducting needs analysis, planning, developing initial products, expert testing (BK material experts & media experts), results of expert testing and testing of potential product users (counselors), product revisions, field testing initial and final product revision of the simulation game guide and simulation game media, based on the results of data analysis of assessments by experts and potential users, it can be concluded that this simulation game guide for counselors and simulation game media is very appropriate, very useful, very easy, and very interesting. Therefore, the self-disclosure simulation game for junior high school students is very suitable for use as a guidance service by counselors for students.